2011
DOI: 10.1159/000329040
|View full text |Cite
|
Sign up to set email alerts
|

I-CLIP: Improved Stratification of Advanced Hepatocellular Carcinoma Patients by Integrating Plasma IGF-1 into CLIP Score

Abstract: Objective: Improving the prognostic stratification of unresectable hepatocellular carcinoma (HCC) patients is critically needed. Since patients’ survival is closely linked to the severity of the underlying liver disease, and insulin-like growth factor-1 (IGF-1) is produced predominantly in the liver, we hypothesized that IGF-1 may correlate with patients’ survival and hence improve the prognostic ability of the Cancer of the Liver Italian Program (CLIP) score. Methods: Baseline plasma IGF-1 and clinicopatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…The associations were independent of other clinicopathologic variables such as hepatitis etiologies, performance status, a-fetoprotein levels, and CLIP scores. Although previous studies have shown that blood IGF-1 levels are a prognostic marker for HCC (13,14,22), this is the first study showing the potential association between serum IGF-1 levels and the efficacy of systemic therapy for advanced HCC. The study was a retrospective analysis and did not include a control group of patients who did not receive therapy.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The associations were independent of other clinicopathologic variables such as hepatitis etiologies, performance status, a-fetoprotein levels, and CLIP scores. Although previous studies have shown that blood IGF-1 levels are a prognostic marker for HCC (13,14,22), this is the first study showing the potential association between serum IGF-1 levels and the efficacy of systemic therapy for advanced HCC. The study was a retrospective analysis and did not include a control group of patients who did not receive therapy.…”
Section: Discussionmentioning
confidence: 76%
“…However, patients with HCC had lower circulating IGF-1 levels than healthy controls (10). On the basis of an HCC patient cohort with heterogeneous disease status and treatment, Kaseb and colleagues found that low plasma IGF-1 levels were associated with extensive liver involvement, vascular invasion, and poorer OS (13,14). Most circulating IGF-1 is produced in the liver (3,4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, our results are consistent with recent studies of the levels of circulating IGF-I and prognosis in patients with hepatocellular carcinoma. Kaseb and colleagues showed that lowplasma IGF-I levels were associated with advanced clinicopathologic factors and shorter OS in patients with heterogeneous stages of hepatocellular carcinoma (11,21). Similarly, low-baseline serum IGF-I levels correlated with poor treatment response, progression-free survival, and OS in patients who received antiangiogenic therapy for advanced hepatocellular carcinoma (12).…”
Section: Discussionmentioning
confidence: 99%
“…In this group of patients, the BCLC classification correlates best with survival than other staging systems and their survival rates are better due to the possibility of providing curative treatment of larger lesions in turn, leading to decreased recurrences (27% vs 73%) and greater survival (81% vs 23%) [116,117] . Upon recent inclusion of molecular markers such as wtER, IGF and VEGF-1 in prognostic scoring systems such as CLIP, their precision has been favorable although they are not currently routinely used [118][119][120] .…”
Section: Prognosismentioning
confidence: 99%